Local Fractional Laplace Variational Iteration Method for Solving Nonlinear Partial Differential Equations on Cantor Sets within Local Fractional Operators - Jafari, Hossein; Jassim, Hassan Kamil (Sulaimani Journal for Pure and Applied Sciences, 2014)
In this work, we discuss solutions of the nonlinear partial differential equations on Cantor sets within local fractional operators. The nondifferentiable approximate solutions are obtained by using the local fractional Laplace variational iteration method, which is the coupling method of local fractional variational iteration method and Laplace transform. The obtained results show the efficiency and accuracy of implements of the present method.
Keywords: Nonlinear differential equation Fractional Gas dynamics equation Cantor setYangLaplace transform local fractional variational iteration method